Blocking FSH Induces Thermogenic Adipose Tissue and Reduces Body Fat. Issue 10 (October 2017) - Liu, Peng; Ji, Yaoting; Yuen, Tony; Rendina-Ruedy, Elizabeth; DeMambro, Victoria E.; Dhawan, Samarth; Abu-Amer, Wahid; Izadmehr, Sudeh; Zhou, Bin; Shin, Andrew C.; Latif, Rauf; Thangeswaran, Priyanthan; et al.
Abstract : (Abstracted from Nature 2017;546:107–112) Osteoporosis is common in postmenopausal women because of cessation of menstruation. Bone loss occurs most rapidly during late perimenopause—a period characterized by relatively stable estrogen and rising follicle-stimulating hormone (FSH) levels as a result of ovarian failure.